3.0T, time‐resolved, 3D flow‐sensitive MR in the thoracic aorta: Impact of k‐t BLAST acceleration using 8‐ versus 32‐channel coil arrays. Issue 2 (2nd December 2014) - Zaman, Arshad; Motwani, Manish; Oliver, James J.; Crelier, Gerard; Dobson, Laura E.; Higgins, David M.; Plein, Sven; Greenwood, John P.
<x xml:space="preserve">Abstract</x> Purpose To evaluate the performance of 4D flow MR in the thoracic aorta with 8‐ and 32‐channel coil arrays using k‐t BLAST and SENSE acceleration techniques and compare this to a conventional 2D SENSE approach. Materials and Methods Fifteen healthy subjects and eight patients underwent magnetic resonance imaging (MRI) at 3.0T using: 1) 2D SENSE phase contrast velocity mapping as the reference standard and 2) 4D‐flow pulse sequences accelerated with SENSE and k‐t BLAST, using both 8‐ and 32‐channel coil arrays. Data processing was performed using GT Flow. Image quality of the magnitude images and pathline visualization were graded and mean scan times, flow, peak velocity, stroke volume, and image quality were compared between techniques. Results Mean scan times were significantly lower for 4D‐flow sequences accelerated with k‐t BLAST compared to SENSE (5.5 vs. 25.2 min; P < 0.01). 4D k‐t BLAST acquisition had greater magnitude and pathline image quality than 4D SENSE acquisition for both 32‐channel and 8‐channel data (P < 0.001); both 4D SENSE and 4D k‐t BLAST acquisitions had significantly greater image quality when 32 channels were utilized compared to 8 (P < 0.05). On Bland–Altman analysis, all 4D flow pulse sequences showed significant agreement with the 2D SENSE reference for peak velocity measurement (P > 0.05); the lowest bias being observed with the 4D 32 channel k‐t BLAST sequence. There were no significant differences in measured flow, peak velocity, or stroke volume with any of the four investigated 4D acquisition techniques compared to reference technique values (P > 0.05). In patients, there were no significant differences in flow, peak velocity, or stroke volume measurements between 32‐channel 4D k‐t BLAST and the reference acquisition. Conclusion 4D flow MR using k‐t BLAST and 32 channel coils allows a reduction in total scan time while improving overall image quality compared to a standard 2D SENSE and 4D SENSE acquisitions. The use of 32 channels rather than 8 channels with the 4D k‐t BLAST was also preferable in terms of image quality. J. Magn. Reson. Imaging 2015;42:495–504.